CAP-ACP Workload Model for Advanced Diagnostics in Precision Medicine. Issue 1 (23rd February 2022) - Park, Paul C; Kurek, Kyle C; DeCoteau, John; Howlett, Christopher J; Hawkins, Cynthia; Izevbaye, Iyare; Carter, Michael D; Redpath, Margaret; Lo, Bryan; Alex, Deepu; Yousef, George; Yip, Stephen; et al.
Abstract: Objectives: In precision medicine, where oncologic management is tailored to the individual's clinical and genetic profiles, advanced diagnostic testing provides prognostic information and guides management in a growing number of malignancies. There is a need to capture the work pathologists perform to meet this demand by providing medically relevant, timely, and accurate testing results. This work includes not only direct patient consults (interpretation of results and issuing reports) but the administrative and medical oversight as well as the research needed to provide the necessary quality assurance, quality control, direction, and framework for the laboratory. Methods: An expert panel of Canadian pathologists involved in advanced diagnostics was convened to establish and beta test a model for workload assessment in advanced diagnostics. Results: All aspects of the advanced diagnostics workload were detailed and applied to models based on members' experience, including medical oversight, administration, and the introduction of new testing and platforms. Models for biomarker testing were developed for simple and complex or multiplexed assays, and a detailed model was developed to assess the workload for next-generation sequencing–based assays. Conclusions: This paper provides the first detailed proposal for capturing an advanced diagnostic workload to enable appropriate pathologist allotment for performing all the steps required to run an advanced diagnostic service.